The effect of Testis compositum in the treatment of Acne vulgaris - Bekker, Marelize (2013)
M.Tech. (Homoeopathy) === Acne vulgaris is a common skin condition, affecting mostly adolescents. This study attempts to demonstrate the effect of the homoeopathically prepared remedy Testis compositum in the treatment of acne vulgaris. Thirty participants were selected for the study, but only 28 completed the study. The study was conducted over a period of 8 weeks. All the participants formed the control group during the first two weeks of the study, and then formed the experimental group for the next six weeks. During the control period, the participants received placebo medication. At the start of the control period, and at two week intervals through the duration of the study, the participants were assessed by counting the acne lesions – only facial Acne vulgaris was assessed during the trial. At the start of the control period, the start of the experimental period, and after completion of all treatment, frontal and bilateral facial photographs were taken to enable visualisation of the changes that occurred during the study. The results were statistically analysed using the t-test, the Wilcoxon test and descriptive statistics. The results show that treatment with Testis compositum had a significant effect in improving acne vulgaris.